Implementation Good Governance in Public Service Immigration in Service Passport Making - Nadia Mahza Prameswari (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
Public services are government efforts to meet needs of citizens in form of goods and services that can improve welfare of society. In context of passport making services, application of good governance principles is very important to ensure optimal service quality. Good governance includes aspects of openness, accountability, and transparency in implementation of public services. This study aims to analyze application of good governance in public services in field of immigration, especially in process of making passports in Indonesia. This research method uses normative juridical approach with qualitative data analysis. Data was collected through literature study which includes legislation, official documents, and Related Literature. Results showed that implementation of good governance in Directorate General of immigration has undergone various innovations, such as One stop service System, Easy Passport, and M-passport application, to improve efficiency and transparency in passport making process. However, there are still some obstacles, such as poor network quality and public complaints about service. However, new policies implemented, such as Easy Passport Service and One stop service, have made it easier and increased public satisfaction. In conclusion, although implementation of good governance in passport-making services has shown improvement, ongoing efforts are still needed to overcome problems and improve service quality in order to achieve better public satisfaction.